Implementation of Schottky Barrier Diodes (SBD) in Standard CMOS Process for Biomedical Applications - Cabral, David Sebastiao; Moreno, Robson Luiz; Pimenta, Tales Cleber; Zoccal, Leonardo Breseghello; Crepaldi, Paulo Cesar (IntechOpen, 2012)
None